STANDARDIZATION AS A TOOL FOR ENSURING THE QUALITY OF HIGHER PEDAGOGICAL EDUCATION - Iliichuk, Liubomyra (Continuing Professional Education: Theory and Practice, 2025)
The article considers standardization as a key tool for ensuring the quality of higher pedagogical education in the context of the transformation of the modern educational space. The aim of the study is to theoretically substantiate the potential of standardization based on an analysis of the regulatory framework and educational programs in the field of primary education. The essence of the concept of «standardization» in the context of higher pedagogical education is defined, and its role in ensuring the quality of professional training for future primary school teachers is revealed. Within the framework of the study, a comparative analysis of educational and professional programs in the specialty «Primary Education» implemented in Ukrainian higher education institutions was carried out to assess their compliance with the current standard of higher education. The results of the analysis showed the overall structural uniformity of the programs, while identifying content variability, which is manifested in the formulation of special (professional) competencies, the specifics of educational components, and approaches to the design of program learning outcomes. It was established that such variability is due to the integration of state regulatory requirements with author’s conceptual approaches that reflect institutional development strategies, regional context, and stakeholder demands. It is justified that standardization in the field of training primary education specialists performs not only a regulatory but also a strategic function, ensuring the unity of educational goals and results, while preserving academic autonomy, content flexibility, and the ability of educational programs to adapt in conditions of dynamic change. A conclusion has been formulated about the formation of an educational environment in Ukraine which, while maintaining its focus on standardized requirements, is distinguished by its content variability and ability to respond quickly to stakeholder requests and current vectors of transformation in the modern educational space.